2003
DOI: 10.1097/00004872-200305000-00022
|View full text |Cite
|
Sign up to set email alerts
|

Increased renal vascular sensitivity to angiotensin II in hypertension is due to decreased response to prostaglandins

Abstract: These findings indicate that young human subjects with a positive family history of hypertension have a defective vasodilator prostaglandin system, which is responsible for increased renal vascular sensitivity to angiotensin II. Enhanced renal vasoconstriction may be an early event leading to the generation of primary hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2005
2005
2009
2009

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 31 publications
0
12
0
Order By: Relevance
“…In addition, reduced responsiveness to vasodilator prostaglandins may result in a greater sensitivity to Ang II, at least in the kidney. 53 However, whether the kallikrein-kinin system plays any role in the regulation of basal vascular tone remains open to debate. Under a variety of circumstances, blockade of bradykinin receptors has no or only minimal effects, and it seems quite possible that increased activity of the kallikrein-kinin system stems from its interaction with the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reduced responsiveness to vasodilator prostaglandins may result in a greater sensitivity to Ang II, at least in the kidney. 53 However, whether the kallikrein-kinin system plays any role in the regulation of basal vascular tone remains open to debate. Under a variety of circumstances, blockade of bradykinin receptors has no or only minimal effects, and it seems quite possible that increased activity of the kallikrein-kinin system stems from its interaction with the renin-angiotensin system.…”
Section: Discussionmentioning
confidence: 99%
“…The debate toward the consequence side stems from the observations that endothelial dysfunction is found in all forms of HTN, increases with increases in BP, and is partly reversed by antihypertensive therapy. Other studies have demonstrated that adult SHR have both endothelial dysfunction and overt HTN, while young SHR have endothelial dysfunction but normal BP, suggesting that endothelial dysfunction may be a cause rather than a consequence of HTN (124). Endothelial cell dysfunction involves an imbalance in the release of vasodilatory mediators, such as NO, PGI 2 , and endothelium-derived hyperpolarizing factor (EDHF), and vasoconstrictive mediators, such as ET, ANG II, and thromboxane A 2 (TxA 2 ) (Fig.…”
Section: Renal Endothelial Cell Dysfunction In Htnmentioning
confidence: 98%
“…On the other hand, increased medullary BP or flow induces the renal medullary interstitium and collecting ducts to release PGE 2 . Young humans with a family history of HTN have defective vasodilator prostaglandin system and thereby increased renal vasoconstriction sensitivity to ANG II (124).…”
Section: Renal Endothelial Cell Dysfunction In Htnmentioning
confidence: 99%
“…We have shown previously [6] that these individuals also have an enhanced sensitivity in the renal vasculature to low doses of infused Ang II (angiotensin II). In addition, we have recently observed [7] that the renal vascular sensitivity to Ang II in firstdegree relatives of hypertensives is increased due to a defective prostaglandin response.…”
Section: Introductionmentioning
confidence: 99%